A high-resolution hydrodynamic-biogeochemical coupled model of the Gulf of Cadiz – Alboran Sea region. - MACIAS, D. M.; GUERREIRO, C. T.; PRIETO, L.; PELIZ, A.; RUIZ, J. (Mediterranean Marine Science, 2014)
The southern Iberia regional seas comprise the Gulf of Cadiz and the Alboran Sea sub-basins connected by the narrow Strait of Gibraltar. Both basins are very different in their hydrological and biological characteristics but are, also, tightly connected to each other. Integrative studies of the whole regional oceanic system are scarce and difficult to perform due to the relative large area to cover and the different relevant time-scales of the main forcings in each sub-basin. Here we propose, for the first time, a fully coupled, 3D, hydrodynamic-biogeochemical model that covers, in a single domain (~2km resolution) both marine basins for a 20 years simulation (1989-2008). Model performance is assessed against available data in terms of spatial and temporal distributions of biological variables. In general, the proposed model is able to represent the climatological distributions of primary and secondary producers and also the main seasonality of primary production in the different sub-regions of the analyzed basins. Potential causes of the observed mismatches between model and data are identified and some solutions are proposed for future model development. We conclude that most of these mismatches could be attributed to the missing tidal forcing in the actual model configuration. This model is a first step to obtain a meaningful tool to study past and future oceanographic conditions in this important marine region constituting the unique connection of the Mediterranean Sea with the open world’s ocean.